Dissecting Slang Words in the Album of 'Kirk' by DaBaby - I Komang Sidny Darma Yadnya; Made Detriasmita Saientisna; Sang Ayu Isnu Maharani (Lembaga Pengembangan Kinerja Dosen, 2026)
This undergraduate thesis entitled Dissecting Slang Words in the Album of ‘Kirk’ by DaBaby examines the types and functions of slang expressions in DaBaby’s lyrics. Adopting Allan and Burridge’s (2006) sociolinguistic framework, the research identifies and categorizes slang types, for instance Fresh and Creative, Clipping, Imitative, Acronym, and Flippant as well as analyses their communicative functions within hip-hop culture. Data were collected from all 13 songs on the Kirk album using qualitative methods. A total of 52 slang expressions were systematically classified and evaluated to determine their roles in expressing identity, emotion, resistance, humor, and social bonding. The findings reveal the Fresh and Creative slang (e.g., drip, vibez, bop) is the most prevalent (41.6%), highlighting DaBaby’s linguistic innovation. Clipping(e.g., gon’, ‘em,) and Imitative (e.g., finna, wanna) types support rhythmic flow and cultural authenticity, while Flippant terms (e.g., nigga, hoe) convey emotional intensity and in-group solidarity. Functionally, slang primarily reinforces group identity and enables emotional expression, with secondary roles in humor, resistance, and social intimacy. This research underscores slang’s significance in hip-hop as a tool for cultural representation, artistic creativity, and generational discourse. It contributes to sociolinguistic studies of music by demonstrating how informal lexicon shapes artist identity and listener engagement in contemporary rap.